Functional outcome of the three-stitch technique of humerus nailing for comminuted shaft humerus fractures - Sachin Kale; Bhushan Patil; Garvit Khatod; Pramod Bhor; Gursimran Sandhu; Venkatsh Jyoti; Rohan Baruah; Sachiti Kale; Rahul Ghodke; Joydeep Dey (MGM Journal of Medical Sciences)
Background: Intramedullary nailing for comminuted shaft humerus fractures has emerged as an innovative and advantageous surgical approach, particularly in cases with significant soft tissue injuries complicating open reduction and internal fixation. This study underscores the benefits of minimally invasive intramedullary humerus nailing to mitigate perioperative and postoperative complications. Materials and Methods: This prospective study was conducted at Dr. D.Y. Patil Medical College and Hospital, Navi Mumbai, Maharashtra, India, from March 2022 to March 2024. Informed consent was obtained from all patients, detailing the study’s methodologies and potential complications. Employing a three-stitch technique, we treated 24 adult patients with posttraumatic comminuted humerus shaft fractures through antegrade humerus nailing, encompassing injuries classified up to type 12C according to the Arbeitsgemeinschaft für Osteosynthesefragen/Orthopedic Trauma Association classification. Results: Among the 24 patients, 22 exhibited excellent functional outcomes and good adherence to the rehabilitation regimen. Two patients encountered delayed wound healing; one underwent vacuum-assisted closure therapy, ultimately achieving satisfactory healing after a series of dry dressings over 2–3 weeks. There were no instances of nonunion. Over 6 months, 22 out of 24 patients experienced significant restoration of function, evidenced by an improvement in Mayo Elbow Performance Index scores from 18 to 23 within the excellent outcome group. University of California at Los Angeles scores also exhibited enhancement, with ratings ranging from exceptional to good, increasing from 20 to 23. Only two patients experienced delayed wound healing, and none suffered from nonunions. Conclusion: Our findings suggest that the three-stitch technique presents a viable alternative to external fixators and other plate osteosynthesis methods in the surgical management of comminuted injuries. This approach yields favorable outcomes with reduced complications and improved cosmetic results.